4(x-3)+0.6=2(x+18)-1.2

Simple and best practice solution for 4(x-3)+0.6=2(x+18)-1.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+0.6=2(x+18)-1.2 equation:



4(x-3)+0.6=2(x+18)-1.2
We move all terms to the left:
4(x-3)+0.6-(2(x+18)-1.2)=0
We multiply parentheses
4x-(2(x+18)-1.2)-12+0.6=0
We calculate terms in parentheses: -(2(x+18)-1.2), so:
2(x+18)-1.2
We multiply parentheses
2x+36-1.2
We add all the numbers together, and all the variables
2x+34.8
Back to the equation:
-(2x+34.8)
We add all the numbers together, and all the variables
4x-(2x+34.8)-11.4=0
We get rid of parentheses
4x-2x-34.8-11.4=0
We add all the numbers together, and all the variables
2x-46.2=0
We move all terms containing x to the left, all other terms to the right
2x=46.2
x=46.2/2
x=23+0.2/2

See similar equations:

| 7x-1+80+6x-37x=180 | | 4(3x+1x)+7-5x=8(-5)(5x-6x)+23 | | 9f=918 | | w/28=17 | | 5h=100 | | 5^(2x+3)=4 | | 78=2z | | y^2+28y+60=0 | | 8+5^(2x+3)=12 | | 130+10x=18x | | x+(x+5)+1/3x=0 | | y/5.5=90 | | 1.3c+5.2=6.4 | | G(-2)=3x-1 | | 2p-5p=3 | | 4+2x-3x=-2 | | 130+20x=36x | | 65+10x=18x | | 130+20x=18x | | 4x^2+11x-6=x^2-2 | | 114=5-(2-x) | | Z=6-3x | | 130=18x | | 3-3a-4=-5 | | 5(2.5^x)=10 | | x2−6x−12=0 | | f=33/2(50) | | f=33/2(50)+9.24 | | Z=p | | 0.12x+56-(2830/x^2)=0 | | 15x=56+8x | | 1/8x+8=11 |

Equations solver categories